HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN GAMBARAN DIRI PADA PENYANDANG CACAT FISIK DI PUSAT REHABILITASI TERPADU PENYANDANG CACAT DAERAH ISTIMEWA YOGYAKARTA - , HANIF NUR ROSYIDA; , Ibrahim Rahmat, S.Kp., S.Pd., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Physical changes that experienced by the disabled is certainly very shaken their mind. This often cause a negative body image. Body image is complex and influenced by several factors. One of the factors that affect a person's body image is social support. Objective: To analyze association between social support from aspect of quantity of support givers and satisfaction in receiving support and body image of the disabled at Pusat Rehabilitasi Penyandang Cacat Daerah Istimewa Yogyakarta (PRTPC DIY). Methods: This study was analytic correlation with cross sectional design carried out in April 2013. Subject of the study consisted of 45 disable persons at PRTPC DIY chosen with simple random sampling technique. Research instrumens were Body image questionnaire and Social Support Questionnaire (SSQ). Data analysis used Pearson Product Moment. Result: Most of respondents (55,6%) had positive body image